(untitled) (Fiep Bulletin - online, 2011)
The aging of the Brazilian population has been accompanied by changes in family structure, increasing demand for long-stay institutions as an alternative to social support for the elderly. This is a descriptive and exploratory study that aims to analyze the quality of life (QOL) of institutionalized elderly in Natal, Brazil. For data collection, interviews with 43 elderly people were conducted using the WHOQOL-OLD module, specifically to evaluate QOL in the elderly. The results showed an overall mean score of 52.9%. The sensory facet obtained the highest mean scores (68.1%), showing satisfaction of the elderly with their situation. However, the autonomy facet presented the lowest mean (40.7%), demonstrating dissatisfaction with the ability to make decisions. It was concluded that the elderly rated their QOL as neither unsatisfactory nor satisfactory. It is necessary to implement public policies aimed at promoting attention to the institutionalized elderly in anticipation of a better quality of life for these people.